Efek steaming up menggunakan Gliricidia sepium pada kambing perah selama masa periode kering terhadap pertumbuhan anak Kambing Peranakan Etawah - Dharmawan, Rachmad; Surjowardojo, P.; Susilorini, T. E. (Faculty of Animal Science, Universitas Brawijaya, 2019)
The study was conducted to evaluate the effect of steaming up using Gliricidia sepium in dry period on the performanceof Etawah Crossbred goats kid production. Twelve goats were selected based on lactation period with the following treatments: (1) T0 as a control, (2) T1 as a treatment for steaming up 0.4% DM, and (3) T2 as a steaming up 0.8% DM. All experiment restricted to the same basal concentrate diet 0.9% DM and ad-libitum of Pennisetum purpureum. The obtained data were analyzed using analysis of variance. The difference in data was analyzed by Duncan's Multiple Distance Test. The result was T2 treatment had a low level of weight loss and BCS at parturition compared to T0 and T1, but had no significant different (P>0.05). Birth weight, weaning weight, and ADG of goats kid were not significantly different between the treatments (P>0.05). The conclusion of this study is that steaming up using Gliricidia sepium by 0.8% based on DM needs in the dry period showed a low decrease in the rate of body weight and low BCS. The steaming up treatment also shows the highest birth weight, weaning weight, and highest ADG.